2019
DOI: 10.14715/cmb/2019.65.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Indole itself and its novel derivative affect PML cells proliferation via controlling the expression of cell cycle genes

Abstract: Recently the role of indole and pyran rings in carcinogenesis has been well studied. Here we studied the effects and the possible mechanisms of the action of basal indole (I3A) and its novel indole derivative (C19H15F3N2O) on inhibition of proliferation cells in acute promyelocytic leukemia NB4 cell line by examining the expression of cell cycle genes. We treated NB4 cells with concentration of C19H15F3N2O for 24-72 h. The MTT and PI/Annexin V examinations were employed for assessment of the proliferation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…We use UPLC-Q-TOF-MS to analyze the composition of EECR; a total of 21 compounds were identified by comparing the mass fragmentations of each metabolite with databases. Recent researches show that Indole, Isoalantolactone, and Aromatic-turmerone in EECR have anti-tumor activities [39–41]. Despite the fact that deep study is needed, these researches still provide support for our research.…”
Section: Discussionmentioning
confidence: 83%
“…We use UPLC-Q-TOF-MS to analyze the composition of EECR; a total of 21 compounds were identified by comparing the mass fragmentations of each metabolite with databases. Recent researches show that Indole, Isoalantolactone, and Aromatic-turmerone in EECR have anti-tumor activities [39–41]. Despite the fact that deep study is needed, these researches still provide support for our research.…”
Section: Discussionmentioning
confidence: 83%
“…The blockade of cell cycle progression by chemotherapeutic agents has always been an ideal choice for developing anticancer therapeutics, and many cytotoxic compounds exert their inhibitory effect by arresting the cell cycle at a specific checkpoint [ 19 ]. Noroozi and colleagues [ 20 ] analyzed the effects of two indole compounds on the inhibition of proliferating cells in acute promyelocytic leukemia (NB4 cell line) by examining the cell cycle, and they demonstrated that both indoles induced apoptosis, thereby facilitating cell cycle arrest. In our work, we found that the four benzo[ f ]indole-4,9-dione derivatives induced cell cycle arrest at the G2/M phase.…”
Section: Discussionmentioning
confidence: 99%
“…The β-actin was used as a reference gene, and the expression of target genes relative to its expression. Relative expression was calculated using the comparative 2 -ΔΔCt formula (Noroozi et al, 2019).…”
Section: Real-time Pcrmentioning
confidence: 99%